2021
DOI: 10.3390/admsci11020044
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Top Managers in Implementing Corporate Sustainability—A Systematic Literature Review on Small and Medium-Sized Enterprises

Abstract: This systematic literature review investigates whether corporate sustainability (CS), according to the tribble bottom line concept (TBL), is implemented in small and medium-sized enterprises (SMEs) and further identifies associated drivers. Building on upper echelon theory (UET) and the Schwartz value system (SVS) this study aims to analyze and contextualize extant empirical research. We developed a PRISMA-based framework to select relevant studies systematically. Based on an initial sample of 1249 articles be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 95 publications
(189 reference statements)
0
9
0
Order By: Relevance
“…This is a well-known method for conducting a literature review on sustainability issues, as well as economic and social sciences [81][82][83][84]. Systematic reviews [15,74,81,82,[84][85][86][87][88][89][90][91] and meta-analyses [92,93] are essential tools to accurately and reliably summarize the evidence [80].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a well-known method for conducting a literature review on sustainability issues, as well as economic and social sciences [81][82][83][84]. Systematic reviews [15,74,81,82,[84][85][86][87][88][89][90][91] and meta-analyses [92,93] are essential tools to accurately and reliably summarize the evidence [80].…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of only empirical articles is due to the inclusion of statistically validated factors that determine GBE. This approach is used in the literature in the PRISMA method when applying SLR to areas, such as medicine [86,[94][95][96][97], management [88,98], consumer behavior [99], tourism [100], and others [81,85,90]. The SLR search of five databases yielded 3393 publications.…”
Section: Conducting the Slrmentioning
confidence: 99%
“…The Upper Echelons Theory shows that leadership, especially sustainable leadership, is an essential factor of corporate sustainability (CS, Corporate Sustainability) [66][67][68]. Among CS research, by a comprehensive investigation of 1249 works within the literature from 2000 to 2020, the study [69] concluded that top managers are the great driving force…”
Section: Internal Perception and Corporate Behaviormentioning
confidence: 99%
“…The Upper Echelons Theory shows that leadership, especially sustainable leadership, is an essential factor of corporate sustainability (CS, Corporate Sustainability) [66][67][68]. Among CS research, by a comprehensive investigation of 1249 works within the literature from 2000 to 2020, the study [69] concluded that top managers are the great driving force and pioneers of corporations engaged in responsible social and environmental practice. Previous studies have shown that leaders with stronger green perceptions are more likely to promote green behavior change in corporations [69][70][71].…”
Section: Internal Perception and Corporate Behaviormentioning
confidence: 99%
“…In contrast, CEOs generally do not influence this decision-making process [10]. Accordingly, it is undeniable that the CFO greatly influences a firm's decisions and development [11,12].…”
Section: Introductionmentioning
confidence: 99%